Деструкція політичної влади, як наслідок конфлікту в транзитному суспільств - Завгородня, Юлія Володимирівна; Завгородня, Ю. В.; Завгородняя, Юлия Владимировна; Zavhorodnia, Yuliia V. (Одеса: Фенікс, 2018)
Політична влада є вершиною системи управління суспільством. Нестабільність у політичній владі призводить до хаосу у державі та породжує руйнування політичної системи. Однією із причин руйнування влади є конфлікти, які перешкоджають демократичному та політичному режиму. Цінність упорядкованості зв’язків між соціальними інститутами потребує практичного втілення. Держава у перехідному стані потребує аналізу мети та напрямків дії влади і громадян. Окрім того, влада вдається до маніпуляцій з метою отримання власної вигоди, тим самим зменшує довіру населення та підриває авторитет до управлінської сфери суспільства.

Политическая власть является вершиной системы управления обществом. Нестабильность в политической власти приводит к хаосу в государстве и порождает разрушение политической системы. Одной из причин разрушения власти являются конфликты, которые препятствуют демократическому и политическому режиму. Ценность упорядоченности связей между социальными институтами, требует практического воплощения. Государство в переходном состоянии требует анализа цели и направлений действия власти и граждан. Кроме того, власть прибегает к манипуляциям с целью получения собственной выгоды, тем самым уменьшает доверие населения и подрывает авторитет к управленческой сфере общества.

Political power is the top of the system of social management. Instability in political power leads to chaos in the state and causes the destruction of the political system. One of the reasons for the destruction of power is the conflicts that interfere with a democratic political regime. The value of ordering relations between social institutions requires practical implementation. A state in transition needs to analyze the purpose and directions of action of the authorities and citizens. In addition, the authorities resort to manipulations in order to obtain their own benefits, thus reducing the trust of the population and undermining the authority of the managerial sphere of society. In the scientific circulation and practical implementation, the term “destruction of power” is constantly being heard, which includes processes of fundamental changes in order to improve the political system. A government apparatus that does not want to adapt to modern changes in any way tries to extend its power but during such actions, the interests of the whole society are undermined. Conflict struggle is the main reason that inhibits the development of Ukrainian society. There are no positive aspects of the conflict when it comes to finding a solution to it.
Завгородня Ю. В. Деструкція політичної влади, як наслідок конфлікту в транзитному суспільств / Ю. В. Завгородня // Актуальні проблеми політики : зб. наук. пр. / редкол.: С. В. Ківалов (голов. редкол.), Л. І. Кормич (голов. ред.), А. В. Полухіна (відп. ред.) [та ін.] ; НУ «ОЮА», Південноукр. центр гендер. проблем. – Одеса : Фенікс, 2018. – Вип. 62. – С. 174-182.
Keywords: політичний конфлікт; деструкція; протиборство; політична влада; транзитне суспільство; политический конфликт; деструкция; противоборство; политическая власть; транзитное общество; political conflict; destruction; confrontation; political power; transit society; Research Subject Categories::LAW/JURISPRUDENCE